Asymmetric and Diffuse Uptake of Left Femur in a 3-Year-Old Child Bone Scan: An Unusual Aspect in Acute Lymphoblastic Leukemia. (January 2016) - Morel, Olivier; Ungureanu, Constantin; Padoin, Pierre; Laurent, Romain; Boulahdour, Hatem
Abstract : Abstract: Acute leukemia is a severe disease frequently encountered in childhood, often diagnosed in later stages because of nonspecific symptoms. It is known to produce uptake in bone scan, and previously described patterns have shown symmetrical abnormalities. However, we report the unusual aspect of the bone scan in a 3-year-old child who was referred to explore an isolated pain of his lower left limb, with hyperthermia and markers of inflammation. A bone scan showed an intense, asymmetrical uptake of the entire left femur. A few days later, his blood count showed circulating blast cells, leading to the diagnosis of leukemia.